Factors Affecting Purchase Decision of Halal Processed Meat for Muslim Consumers in Semarang - Aulisa Lintang Usmandani; Darwanto Darwanto (UIN Siber Syekh Nurjati Cirebon, 2021)
This research analyzes price perception, product quality, halal awareness, halal certification, and halal marketing as factors affecting purchase decision through purchase intention as an intervening variable. The data collected through a questionnaire survey consisting of 130 Muslim consumers in Semarang who purchased halal processed meat products use Structural Equation Model – AMOS analysis. The results of the analysis show that price perception has an insignificant effect on purchase intention and purchase decision. The product quality has a significant effect on purchase intention and an insignificant effect on purchase decision. Halal awareness has a significant effect on purchase intention and an insignificant effect on purchase decision. Halal certification has a significant effect on purchase intention and an insignificant effect on purchase decision. Halal marketing has a significant effect on purchase intention and an insignificant effect on purchase decision. The effect of mediation, quality product towards purchase decision through purchase intention as an intervening variable can mediate as a full mediation.